In the shadow of policy everyday practices in South African land and agrarian reform - Hebinck, Paulus Gerardus Maria 1953-; Cousins, Ben 1949- (Wits University Press, 2013)
Notions of land and agrarian reform are now well entrenched in postapartheid South Africa. But what this reform actually means for everyday life is not clearly understood, nor the way it will impact on the political economy. In the Shadow of Policy explores the interface between the policy of land and agrarian reform and its implementation; and between the decisions of policy ‘experts’ and actual livelihood experiences in the fields and homesteads of land reform projects. Starting with an overview of the sociohistorical context in which land and agrarian reform policy has evolved in South Africa, the volume presents empirical case studies of land reform projects in the Northern, Western and Eastern Cape provinces. These draw on multiple voices from various sectors and provide a rich source of material and critical reflections to inform future policy and research agendas. In the Shadow of Policy will be a key reference tool for those working in the area of development studies and land policy, and for civil society groups and NGOs involved in land restitution
Title from publisher's bibliographic system (viewed on 30 May 2019)
Keywords: Agrarreform; Bodenreform; Landwirtschaft; Südafrika; Land tenure; South Africa; Land reform; Government policy; South Africa; Commons; South Africa; Right of property; South Africa; Restitution; South Africa; Agriculture; South Africa; Land use, Rural; South Africa; Rural development; South Africa; Aufsatzsammlung